Clinical and experimental rationale for antioxidant therapy of chronic bacterial prostatitis - Oleg I. Bratchikov; Igor A. Tyuzikov; Pavel A. Dubonos (Belgorod National Research University, 2020)
Introduction: Literature data prove the important role of oxidative stress in the pathogenesis of Chronic Bacterial Prostatitis (CBP) and its recurrence, which reduces the effectiveness of standard etiotropic therapy of the disease. Aim of study: To improve the results of the pharmacotherapy of CBP by a comprehensive assessment of oxidative disorders in the prostate gland in a clinical and experimental study to provide evidence for antioxidant support. Material and methods: The results of experimental simulation of CBP in 60 male rats and examination of 90 patients with CBP (average age 38.2 ± 1.4; main group) and 30 clinically healthy men (average age 35.5±1.5; control group), which included history-taking, collecting complaints, questioning, general and special examinations, biochemical, cytological, microbiological, sonographic studies. In some experimental animals and patients with CBP, different modes of pharmacotherapy were tested (antimicrobial monochemotherapy; antimicrobial chemotherapy+zinc picolinate; antimicrobial chemotherapy+L-carnitine tartrate in standard doses). The data were processed using descriptive and comparative statistics. Results and discussion: Clinical and experimental findings showed the compensatory nature of the prostatic oxidative disorders after a standard antimicrobial monochemotherapy of the first episode of CBP and their continued persistence with a high risk of decompensation and development of mitochondrial dysfunction after a course of standard antimicrobial monochemotherapy in CBP recurrence. Zinc deficiency in the patients with CBP was detected on average 2.7 times more often than in the healthy men, so zinc determination in the prostatic fluid and subsequent drug compensation should be considered as first-line diagnostic and treatment measures. In the patients with CBP without zinc deficiency, L-carnitine may be an effective alternative to pharmacological correction of the prostatic oxidative disorders. Conclusion: To increase the effectiveness of standard etiotropic therapy of CBP, simultaneous antioxidant support is necessary, using differentiated administration of antioxidants/antihypoxants (zinc or L-carnitine).